Acute effects of monosodium glutamate addition to whey protein on appetite, food intake, blood glucose, insulin and gut hormones in healthy young men. (1st January 2018) - Anderson, G. Harvey; Fabek, Hrvoje; Akilen, Rajadurai; Chatterjee, Diptendu; Kubant, Ruslan
Abstract: Aims: This study investigated the effects of adding monosodium glutamate (MSG) to carrot soup with or without whey protein, on subjective appetite, food intake (FI) and satiety hormones in healthy young men. Methods: Two experiments were conducted using a repeated-measures, within-subject, crossover design. In exp-1 healthy young men (n = 28) consumed water alone (500 mL), or carrot soup (500 g) with or without MSG (5 g, 1% w/w) or whey protein enriched (36 g) carrot soup with or without MSG (5 g, 1% w/w). Subjective appetite was measured post-treatment and FI measured at a meal at 120 min. In exp-2 (n = 15) the same treatments except for water were used. In addition to subjective appetite and FI, blood glucose, insulin, glucose like peptide 1 (GLP-1), C-peptide and ghrelin were measured. Results: Adding MSG to carrot soup or whey protein enriched carrot soup did not affect FI. However, in exp-1 the addition of both MSG and protein increased fullness, and when MSG was added to carrot soup reduced desire to eat. In exp-2, average post-treatment appetite (5–120 min) was lower after carrot soup with MSG and protein than all other treatments (P < 0.05). In exp-2, carrot soup with MSG and protein, but not with protein alone, increased post-treatment insulin and C-peptide, and lowered blood glucose in comparison to carrot soup with no additions (P < 0.05). Conclusion: Adding MSG alone, or in combination with whey protein, to carrot soups did not affect FI. However, MSG increased fullness and reduced desire to eat, as well as subjective appetite, and when added to protein decreased blood glucose and increased insulin and C-peptide, offering some support for the hypothesis that MSG in the gut signals protein consumption.